Solve for y -y+5=11+5z-3

Math
-y+5=11+5z-3
Subtract 3 from 11.
-y+5=5z+8
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 5 from both sides of the equation.
-y=5z+8-5
Subtract 5 from 8.
-y=5z+3
-y=5z+3
Multiply each term in -y=5z+3 by -1
Tap for more steps…
Multiply each term in -y=5z+3 by -1.
(-y)⋅-1=5z⋅-1+3⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=5z⋅-1+3⋅-1
Multiply y by 1.
y=5z⋅-1+3⋅-1
y=5z⋅-1+3⋅-1
Simplify each term.
Tap for more steps…
Multiply -1 by 5.
y=-5z+3⋅-1
Multiply 3 by -1.
y=-5z-3
y=-5z-3
y=-5z-3
Solve for y -y+5=11+5z-3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top